1994
DOI: 10.1901/jaba.1994.27-131
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Extinction Work: An Analysis of Procedural Form and Function

Abstract: We examined methods for determining how extinction should be applied to different functions of self-injurious behavior (SIB). Assessment data indicated that the head banging of 3 children with developmental disabilities was maintained by different reinforcement contingencies: One subject's SIB was positively reinforced by attention from adults, the 2nd subject's SIB was negatively reinforced by escape from educational tasks, and the 3rd subject's SIB appeared to be automatically reinforced or "self-stimulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
165
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 283 publications
(174 citation statements)
references
References 27 publications
7
165
0
2
Order By: Relevance
“…Moreover, inaccurate interpretation of FA data can lead to the selection of ineffective interventions, and possibly, interventions that exacerbate problem behavior (e.g., Iwata, Pace, Cowdery, & Miltenberger, 1994). Thus, using FAs to guide treatment selection is an important tool for behavior analysts working within applied settings.…”
mentioning
confidence: 99%
“…Moreover, inaccurate interpretation of FA data can lead to the selection of ineffective interventions, and possibly, interventions that exacerbate problem behavior (e.g., Iwata, Pace, Cowdery, & Miltenberger, 1994). Thus, using FAs to guide treatment selection is an important tool for behavior analysts working within applied settings.…”
mentioning
confidence: 99%
“…DESCRIPTORS: attention-maintained problem behavior, competing stimuli, extinction, functional analysis, noncontingent reinforcement Since the emergence of functional analytic methods, treatment of severe behavior disorders using extinction has become considerably more precise (Iwata, Pace, Cowdery, & Miltenberger, 1994). That is, by identifying the specific reinforcers for problem behavior, functional analysis also specifies the contingency that must be discontinued for extinction to occur.…”
mentioning
confidence: 99%
“…We cannot conclude, therefore, that deprivation of attention is a specific or a universal EO for attention-maintained problem behavior. It seems reasonable, however, to suggest that EOs that establish motivation for attention are likely to be particularly involved in attention-maintained (rather than, say, escape-maintained) problem behavior, given the growing literature showing that interventions relevant to the identified consequences of problem behavior are more likely to be effective than irrelevant interventions (see, e.g., Carr & Durand, 1985a;Iwata, Pace, Cowdery, & Miltenberger, 1994;Repp, Felce, & Barton, 1988).…”
Section: Social-positive Reinforcementmentioning
confidence: 99%
“…In practice, this amounts to no longer delivering the reinforcer that previously maintained the behavior (Lerman & Iwata, 1996). Iwata, Pace, Cowdery, and Miltenberger (1994) have recently demonstrated that extinction's success depends upon the correct identification of the reinforcer and have suggested that extinction likely plays a role in a range of other treatments such as differential reinforcement of other behavior and noncontingent reinforcement (Vollmer et al, , 1995. Extinction has been shown to reduce the occurrence of problem behavior, although reduction is sometimes preceded by an extinction burst in which the problem behavior temporarily occurs at rates higher than in baseline (Lerman & Iwata, 1995).…”
Section: Analyzing Existing Treatments From An Eo Perspectivementioning
confidence: 99%